Reversible effects of chaotropic agents on the proton permeability of Escherichia coli membrane vesicles. - Patel, L (1975)
Extraction of E. coli ML 308-225 membrane vesicles with chaotropic agents causes the vesicles to become specifically permeable to protons. As a result, the vesicles no longer generate a membrane potential, interior negative, and they do not catalyze respiration-dependent lactose or proline transport. Treatment of the extracted vesicles with various carbodiimides decreases the permeability of the vesicle membrane to protons, causing them to regain their ability to generate a membrane potential. By this means, active transport is completely reactivated. Exposure of the vesicles to carbodiimides prior to extraction with chaotropic agents makes transport activity impervious to the effects of the chaotropes.